(untitled) (e-Proceedings of the Faculty of Agriculture International Conference, 2024)
This research aims to make stiff dough from water yam and black turtle bean (Akidi) flours and ascertain the quality attributes. The water yam was peeled, sliced while in water, oven dried at 60℃ for 4 h and milled into flour while the black bean was sorted, divided into two equal parts one part was soaked for 5 h while the other was boiled for10 mins and thereafter oven dried at 65 ℃, dehulled and milled into flour. The flour samples were blended at different ratios of water yam to black turtle bean, 100 % water yam flour (WY) served as control, 90:10 (WB1), 80:20 (WB2), 70:30 (WB3), 60:40 (WB4), 50:50 (WB5), 90:10 (WS1), 80:20 (WS2), 70:30 (WS3), 60:40 (WS4) and 50:50 (WS5). The proximate, anti-nutritional and consumer acceptability were assessed. The nutritional compositions of the product all showed significant differences. The flours’ proximate composition revealed the following ranges of results: 1.84 to 5.20% ash, 0.61 to 1.87% crude fat, 0.72 to 2.17% crude fibre, 2.57 to 8.17% moisture, and 71.35 to 81.95% carbohydrate. The antinutritional compositions showed that boiling reduced the phytate and tannin contents to 0.05 mg/100g and 0.06 mg/100g while soaking caused a significant reduction (p<0.05) in the saponin and oxalate contents to 0.06 mg/100g and 0.02 mg/100g respectively. Stiff dough prepared from soaked sample WS1(90:10) had the highest overall acceptability. These findings suggests that water yam/black turtle stiff dough can meet the nutritional demands of the populace. This study provides an alternative way of utilizing water yam and black turtle bean thus preventing post-harvest losses and ensuring eradication of protein energy malnutrition and proper food security.